METHODOLOGICAL STRUCTURE OF JOURNALS WITH HIGH IMPACT FACTOR ACCORDING TO THE SUMMARY AND TRAINING CHARACTER - ARGOTA PÉREZ, George (2021)
The aim of study was to evaluate the introductory methodological structure of journals with a high impact factor according to the summative and formative nature. The percentage of application was estimated according to the following character: summative, formative, comprehensive, scientific and check-evaluative for the last four volumes of five journals with different approaches (Biomedical Sciences, Environmental Sciences, Food y Nutrition, Pharmaceutical Sciences, Research y Reviews: Journal of Educational Studies). Each character was assigned the 25% score before the interpretation of being manifested in the published scientific articles excluding the check-evaluative character due to the fact that it was assumed as the evaluation form that the reviewers should follow, varying the same among the journals. 5% was assigned among the methodological structures: introduction, materials and methods, results, discussion and conclusions. It was observed that the  number of articles published among the numbers of the journals were: 18, 16, 16, 14 and 16 where the order of character corresponded to: scientific> comprehensive> summative> formative. The character by methodological structures was: scientific and comprehensive (introduction), comprehensive (materials and methods), results (scientific, comprehensive), discussion (scientific, comprehensive, and summative) and conclusions (summative, formative).